Microplastic Pollution on the Beaches of the Black Sea in Romania and Bulgaria - Mirel Glevitzky; Gabriela-Alina Dumitrel; Gerlinde Iuliana Rusu; Daniela Toneva; Stoyan Vergiev; Mihai-Teopent Corcheş; Ana-Maria Pană; Maria Popa (Applied Sciences)
Microplastic pollution has gained attention in recent years due to its adverse impact on the environment. As a major threat to marine ecosystems and biota, the accumulation of microplastics along coastlines has become a growing concern. This study focused on quantifying and characterizing the presence, distribution, and composition of microplastics along the beaches of Romania and Bulgaria. Microplastics were extracted from beach sand samples using a saturated NaCl solution. The particles were then analyzed through FT-IR and DSC spectral analyses to identify their chemical composition. Sampling was conducted across several resorts along the Romanian and Bulgarian coastlines. The findings revealed varying concentrations of microplastics across different beaches, with Romanian beaches showing concentrations of between 40 and 213 particles per sample (470–2500 microplastics/kg), which were notably higher in areas like Mamaia and Costinești. On Bulgarian beaches, the average concentrations reached up to 137 particles per sample (1612 microplastics/kg), particularly in areas like Sunny Beach and Nessebar. Polyethylene (PE) was identified as the most prevalent polymer (55%), followed by polyamide (PA), polypropylene (PP), polyethylene terephthalate (PET), and polyurethane (PU). These polymers were linked to common sources such as packaging, textiles, and industrial products. Microscopic examination, combined with FT-IR and DSC spectral analysis, confirmed the plastic nature of the particles, revealing distinct chemical structures characteristic of each material type. This study underscores the widespread contamination of Romanian and Bulgarian beaches with microplastics, emphasizing the environmental risks to coastal ecosystems. The presence of synthetic polymers highlights the urgent need for policies targeting plastic waste management to mitigate the growing pollution in marine environments.